Pengaruh Overhaul Terhadap Kinerja High Pressure Heater Unit 3 PLTU Banten Lontar - Trassanda Scudetto Widestomo Putra; Eri Prabowo; Fikry Ramadani (JTM : JURNAL TEKNIK MESIN, 2026)
This study analyzes the effect of overhaul on the performance of High Pressure Heater (HPH) 1,2, and 3 in unit 3 of PLTU Banten 3 Lontar  at a constant load of 294 MW. The analysis used actual operational data before overhaul (July 2018) and after overhaul (December 2018). Heater Performance was evaluated using terminal temperature difference (TTD), drain cooler approach (DCA), temperature rise (TR), logarithmic mean temperature difference (LMTD), Capacity heat ratio (C), and thermal effectiveness. The result show that overhaul generally improved HPH performance. The strongest improvement occured HPH 1, where DCA decreased from 26.68 celcius to 4.38 celcius, LMTD decreased from 42.81 celcius to 20.62 celcius, and effectiveness increased from 0.72 to 0.95. HPH 2 showed the only TTD improvement from 0.79 celcius to 0.66 celcius, while HPH 1 and HPH 3 experienced slightly higher TTD after overhaul. Even so, the consistent decline in effectiveness for all heaters indicate that tube cleaning, leakage testing, tube plugging, and gasket replacement restored heat transfer performance.  Therefore, overhaul is an effective maintenance action to improve HPH thermal performance with the most significant impact observed in HPH 1